1991
DOI: 10.3109/00016489109138401
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Nerve Growth Factor Receptor in Developing Inner Ear of Rats

Abstract: NGFR-immunoreactivity was first detected in the epithelia of the otic placode at E 10 and the entire epithelium of the otic vesicles was NGFR-immunoreactive at E 11. At this stage no nerve fibers were present in the epithelia and the immunoreactivity was confined to portions of the otic epithelium where the immunoreactive nerve bundles penetrated. As the development proceeded and the organ of Corti was matured, NGFR-immunoreactivity was localized on the plasma membrane of intraepithelial nerve fibers, that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…To date, the formation of the inner sulcus has been supposed to be due to a widespread extinction of tall-columnar cells via transdifferentiation or apoptosis (Hinojosa, 1977). Conversant with other reports (Abe et al, 1991;Von Bartheld et al, 1991), we observed p75 NGFR receptor mRNA in pillar cells and fibers, but also noted this receptor in the GER (Figs. 7 and 8).…”
Section: Ngfr With Morphogenetic Maturationsupporting
confidence: 70%
“…To date, the formation of the inner sulcus has been supposed to be due to a widespread extinction of tall-columnar cells via transdifferentiation or apoptosis (Hinojosa, 1977). Conversant with other reports (Abe et al, 1991;Von Bartheld et al, 1991), we observed p75 NGFR receptor mRNA in pillar cells and fibers, but also noted this receptor in the GER (Figs. 7 and 8).…”
Section: Ngfr With Morphogenetic Maturationsupporting
confidence: 70%
“…This is consonant with the evidence that NGF supports survival of sensory neurons derived from the neural crest, but not of those of placodal origin (30,31), whereas BDNF and NT-3 promote survival of sensory neurons of both of these origins (14)(15)(16)(17)32 A role for NGF in inner ear development has been established from the demonstration ofgp75LNGFR and its mRNA in the innervating neurons and epithelial structures (3)(4)(5). However, gp75LNGFR binds NGF, BDNF, NT-3, and NT-4 with low affinity that is not sufficient to mediate signal transduction (18,20).…”
Section: Discussionmentioning
confidence: 57%
“…In avian and rat embryos, low-affinity nerve growth factor (NGF) receptor (gp75LNGFR) and its mRNA have been localized to the otic placode and otic vesicle, to nonsensory cells of the developing organ of Corti, and to developing inner ear ganglia (3)(4)(5). Binding studies have demonstrated the presence of NGF receptors in the statoacoustic ganglion (SAG) and its target, the otic vesicle (6)(7)(8).…”
mentioning
confidence: 99%
“…Several recent studies indicate that prenatal innervation of the organ of Corti is regulated by members of the neurotrophin family (Despres et al 1988(Despres et al , 1991Abe et al 1991;von Bartheld et al 1991;Represa et al 1991Represa et al , 1993Ernfors et al 1992;Pirvola et al 1992Pirvola et al , 1994Bothwell 1992, 1994;Ylikoski et al 1993). In many sensory and motor systems, members of the neurotrophin nerve growth factor (NGF) family (Levi-Montalcini and Angeletti 1968), brain-derived neurotrophic factor (BDNF; Barde et al 1982); neurotrophin-3 (NT-3; Hohn et al 1990;Maisonpierre et al 1990;Rosenthal et al 1990), and neurotrophin-4 (NT-4/5; Ip et al 1992) are expressed in target cells of developing neurons within several different neuronal populations in various time/space windows (Hallböök et al 1990;Hohn et al 1990;Maisonpierre et al 1990;Ip et al 1992;Elkabes et al 1994).…”
Section: Introductionmentioning
confidence: 99%